THE PUBLIC NATURE OF OBLIGED PARTY OF PUBLIC CONTRACTS - Koryogdiev Bobur Umidjon ugli (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This article investigates the legal nature and theoretical foundations of public contracts within private legal relationships, focusing on the influence of public interest and public activity on contractual obligations. Method: Utilizing a comparative legal analysis approach, the study examines legislative frameworks, judicial interpretations, and scholarly perspectives to elucidate the distinctions between the subject and object of public contracts. Results: The findings reveal significant challenges in defining and applying the concept of “public interest” in private law, highlighting its evaluative and subjective nature. The study underscores the legislative implications of public activity in private relationships, particularly in balancing individual and societal interests while delineating the boundaries of freedom in entrepreneurial activities. Novelty: By providing a comprehensive examination of public interest's role in private law, the article offers new insights into its impact on legal practice, contributing to a deeper understanding of how public contracts shape the interface between public and private legal spheres.